Generic solicitude in sequence-initial position as a practice for pre-closing proposals in Mandarin telephone calls - Dong, Boyu; Wu, Yaxin (East Asian Pragmatics, 2020)
Based on 200 mundane Mandarin Chinese telephone calls, this article describes the composition of generic solicitude in sequence-initial position in the closing section of telephone calls. Two types of generic solicitude are found, namely, stand-alone generic solicitude and composite generic solicitude. Stand-alone generic solicitudes are found in single unit turns and usually occur in imperatives like Adj + dianr + V. The recipients frequently accept the generic solicitude by displaying minimal response followed by a terminal sequence. Composite generic solicitudes occur in multi-unit turns which include closing components and generic solicitudes. The recipients may accept or reject the pre-closing proposal by way of a composite generic solicitude. The generic solicitude could be expanded by both participants. The article concludes that generic solicitude is a practice for pre-closing proposals in Mandarin telephone calls. Generic solicitudes in the closing section of a telephone call function to establish the closing-relevant environment and reaffirm relationship work. This article contributes to our understanding of the organisation of telephone closings in Mandarin interaction.